Zealot : the life and times of Jesus of Nazareth - Aslan, Reza (New York : Random House, 2013)
Presents a meticulously researched biography of Jesus that draws on biblical and historical sources to place his achievements and influence against the turbulent backdrop of his time.
Includes bibliographical references (p. [273]-282) and index.
Keywords: Jesus Christ -- Biography; Jesus Christ -- Biography; Biographies